Experimental validation of the energy ship concept for far-offshore wind energy conversion. (1st November 2021) - Babarit, A.; Abdul Ghani, N.; Brouillette, E.; Delvoye, S.; Weber, M.; Merrien, A.; Michou, M.; Gilloteaux, J.-C.
Abstract: The energy ship is a new concept for offshore wind energy capture. It consists of a wind-propelled ship that generates electricity using water turbines attached underneath its hull. Since it is not grid-connected, the generated energy is stored aboard the ship (for instance, using batteries or through conversion to hydrogen using an electrolyzer). This concept has received little attention until today. Particularly, there had not been yet an experimental proof-of-concept. In order to bridge this gap, an experimental platform has been developed at Centrale Nantes. It consists of a 5.5 m long catamaran equipped with a 240 mm diameter water turbine. The platform was tested in July 2019 on the river Erdre (France). Results show that a full-scale energy ship could deliver high levels of power production (megawatts); and that it is essential to optimize the water turbine induced drag in order to maximize energy production. Highlights: The energy ship is a new technology for offshore wind energy conversion which may enable harvesting the far-offshore wind energy resource. To the authors' knowledge, this paper presents the world-first experimental proof-of-concept of the energy ship technology. It is based on a 18 feet sailing catamaran equipped with a water turbine. Results show that power production may exceed 2 MW at full scale; and that it is key to optimize water turbine drag in order to maximize energy production.